Case report of a vertical straight sinus with hydrocephalus and Chiari I malformation - Hage, Dany (Anat Cell Biol, 2020)
The straight sinus is a division of the dural venous sinuses, found beneath the splenium of the corpus callosum. At the internal occipital protuberance, it comes together with the superior sagittal sinus and transverse sinus to form the torcular Herophili. It functions as a major site of venous drainage for the cerebellum, inferior sagittal sinus, and vein of Galen. Many morphological variations have been reported involving the angulation, positioning, and number of straight sinuses present. Patients with Chiari II and III malformations have been observed to have a high incidence of anatomical variation with their dural venous sinuses, including vertically oriented straight sinuses. Additionally, there is a high rate of hydrocephalus in this patient population. Herein, we report a vertically oriented straight sinus in a child.